2002
DOI: 10.1046/j.1365-2249.2002.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by fenoterol of human eosinophil functions includingβ2-adrenoceptor-independent actions

Abstract: SUMMARYAgonists at b 2 adrenoceptors are used widely as bronchodilators in treating bronchial asthma. These agents also may have important anti-inflammatory effects on eosinophils in asthma. We examined whether widely prescribed b 2 -adrenoceptor agonists differ in ability to suppress stimulus-induced eosinophil effector functions such as superoxide anion (O 2 -) generation and degranulation. To examine involvement of cellular adhesion in such responses, we also investigated effects of b 2 agonists on cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…The drugs that most completely activate a receptor are referred to as full agonists, while those that only partially activate the receptor are referred to as partial agonists. The main effects of β 2 -agonists are considered to be mediated by cAMP-dependent processes and the dependent kinase (protein kinase A; PKA) via adenylylcyclase to prevent inflammatory reactions [14, 16, 22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs that most completely activate a receptor are referred to as full agonists, while those that only partially activate the receptor are referred to as partial agonists. The main effects of β 2 -agonists are considered to be mediated by cAMP-dependent processes and the dependent kinase (protein kinase A; PKA) via adenylylcyclase to prevent inflammatory reactions [14, 16, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several β 2 -agonists suppress allergen-induced recruitment of granulocytes in the lungs and airways [8, 9]. In addition, previous studies indicated inhibitory effects of long-acting β 2 -agonists and adrenergic agonists on granulocyte functions [10,11,12,13,14]. Furthermore, these agents have also been shown to have regulatory effects on the mechanism of bone marrow granulocyte hemopoiesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Procaterol, the synthetic β 2 -adrenoceptor agonist widely used as a bronchodilator in asthma, has been reported to have anti-inflammatory effects on human eosinophils [13, 14]. In this study, we investigated the effect of procaterol on the expression of PPARγ in human eosinophil and its cell line EoL-1.…”
Section: Introductionmentioning
confidence: 99%
“…The ADRB2 gene encodes a beta-2 adrenergic receptor mediating catecholamine-induced activation of adenylate cyclase via G proteins. ADRB2 is a known drug target to treat asthma [92,93] and a number of SNPs in this gene are associated with asthma [94,95] and hypertension [96,97].…”
Section: Prioritization Of Candidate Genesmentioning
confidence: 99%